Perancangan Aplikasi E-Ticketing Pada Agen Bus Berbasis Website Menggunakan Laravel - Muhammad Haidar Wijaya; Magdalena A. Ineke Pakereng (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2021)
Bus is the transportation which is still the main choice for the community which is easilyreached, by buying a ticket through a bus agent the community can enjoy the bus. However, inthe transaction process the customer must visit a bus agent to make a ticket purchase transaction.This is of course very impractical and the tickets that have been purchased are also vulnerable todamage and prone to loss. Therefore, an e-ticketing system is needed to support a more efficienttransaction process and minimize damage and loss of tickets. The laravel framework is used inmaking websites because the laravel framework provides a mail gateway system that makesticketing services easier to customers. The result of designing this application is an e-ticketingwebsite that can help the public in buying bus tickets and minimize damage and loss to tickets.